Interleukin-33 regulates intestinal inflammation by modulating macrophages in inflammatory bowel disease - Dong Hyuk Seo (Nature Portfolio, 2017)
Abstract Interleukin 33 (IL-33) that signals through the ST2 receptor has emerged as a critical modulator in several inflammatory disorders, including inflammatory bowel disease (IBD). However, the precise mechanisms by which IL-33 modulates IBD are controversial. The aim of this study was thus to clarify the role of IL-33 in IBD. The plasma levels of IL-33 were significantly decreased, but soluble ST2 levels were increased in patients with IBD compared to healthy individuals. Moreover, IL-33 restored goblet cell numbers and induced macrophage switching from the M1 to the M2 phenotype. These effects were sufficient to ameliorate colitis in dextran sodium sulfate, trinitrobenzene sulfonic acid, and peritoneal cavity cell transfer models. IL-33 facilitated goblet cell restoration via modulating macrophages toward the M2 phenotype. In addition, wound healing was significantly faster in IL-33-treated human monocyte-derived macrophages than in control cells, which could be attributed to increased polarisation into M2 macrophages. We found that patients with IBD show decreased serum levels of IL-33 compared with healthy individuals and that IL-33 can attenuate colitis and aid tissue repair in mice. The mechanism by which IL-33 exerts these effects appears to involve the stimulation of differentiation of goblet cells and M2 macrophages.